2021
DOI: 10.1007/s10518-021-01147-4
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study on a complex URM building: part II—issues on modelling and seismic analysis through continuum and discrete-macroelement models

Abstract: The paper presents the comparison of the results obtained on a masonry building by nonlinear static analysis using different software operating in the field of continuum and discrete-macroelement modeling. The structure is inspired by an actual building, the "P. Capuzi" school in Visso (Macerata, Italy), seriously damaged following the seismic events that affected Central Italy from August 2016 to January 2017. The activity described is part of a wider research program carried out by various units involved in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…The two FE models agree in terms of smoothed loss of resistance In the same graph a grey band, corresponding to the envelope of the results obtained in Manzini et al (2020) with EF models for the same configuration of the building, is reported; although the peak resistance scatter embeds the corresponding values obtained with software A and B, a major discrepancy with respect to the models employed in the present study is encountered in terms of initial stiffness. It is worth noting that the initial stiffness, as also explained in Castellazzi et al (2021), are set according to a conventional degradation in the case of EF models (assuming a coefficient of reduction of the elastic stiffness equal to 0.5), and considering a progressive degradation associated to the evolution of damage for all the models adopted in this study. Therefore, the difference in terms of initial stiffness can be justified with the different assumptions in terms of elastic mechanical properties and are consistent with the results obtained at the real building scale in Castellazzi et al (2021).…”
Section: Comparisons Of the Results Obtained With The Different Software Packagesmentioning
confidence: 99%
See 2 more Smart Citations
“…The two FE models agree in terms of smoothed loss of resistance In the same graph a grey band, corresponding to the envelope of the results obtained in Manzini et al (2020) with EF models for the same configuration of the building, is reported; although the peak resistance scatter embeds the corresponding values obtained with software A and B, a major discrepancy with respect to the models employed in the present study is encountered in terms of initial stiffness. It is worth noting that the initial stiffness, as also explained in Castellazzi et al (2021), are set according to a conventional degradation in the case of EF models (assuming a coefficient of reduction of the elastic stiffness equal to 0.5), and considering a progressive degradation associated to the evolution of damage for all the models adopted in this study. Therefore, the difference in terms of initial stiffness can be justified with the different assumptions in terms of elastic mechanical properties and are consistent with the results obtained at the real building scale in Castellazzi et al (2021).…”
Section: Comparisons Of the Results Obtained With The Different Software Packagesmentioning
confidence: 99%
“…It is worth noting that the initial stiffness, as also explained in Castellazzi et al (2021), are set according to a conventional degradation in the case of EF models (assuming a coefficient of reduction of the elastic stiffness equal to 0.5), and considering a progressive degradation associated to the evolution of damage for all the models adopted in this study. Therefore, the difference in terms of initial stiffness can be justified with the different assumptions in terms of elastic mechanical properties and are consistent with the results obtained at the real building scale in Castellazzi et al (2021). In addition, the EF models show a higher scatter in terms of initial stiffness with respect to the models here employed, for which the discrepancy is basically negligible.…”
Section: Comparisons Of the Results Obtained With The Different Software Packagesmentioning
confidence: 99%
See 1 more Smart Citation
“…The following three papers are based on 3D complex configurations, inspired by real existing buildings. Ottonelli et al (2021) and Castellazzi et al (2021) analyse a benchmark building based on the P. Capuzi school in Visso, while Degli Abbati et al ( 2021) examines a building inspired by the Pizzoli town hall. These buildings are very interesting being permanently monitored by the Italian Department of Civil Protection and having been hit by the Central Italy 2016-2017 earthquake.…”
mentioning
confidence: 99%
“…Finally, in Occhipinti et al (2021) the comparative study on a 2D multi storey wall is illustrated by focusing on the use of finite and discrete element models.…”
mentioning
confidence: 99%